DISTRIBUIÇÃO E FRACIONAMENTO DO FÓSFORO NOS SEDIMENTOS DOS RIOS BACANGA E ANIL NA ILHA DO MARANHÃO - Nunes, Maria de Lourdes Ferreira (2013)
In the present study it was determined the total stock of phosphorus (PT) in sediments from Anil and Bacanga rivers located on Maranhão island. Additionally, with the aim of assessing the lability of phosphorus in the sediment, it was used sequential chemical extraction according to the protocol of the European Commission (Standards, Measurements and Testing Program). The results indicate PT concentrations ranging from 877.91 to 1466.44 mg. Kgˉ¹, which allows classifying these sediments moderate to highly polluted. The geochemistry of inorganic phosphorus fraction non apatite (PINA) was in mean 32% and the sum of organic fractions (PO) and PINA, considered the greatest lability, showed mean values of 65%, indicating that most of the phosphorus has potential to migrate to interstitial water. Principal component analysis indicates that the PO is proportional to organic matter (OM) and that the silt and clay did not showed good relationship with the fractions PIA and PINA in different sediments. Infrared absorption spectra reveal the intensification of bands in the region between 1200 and 1800 cmˉ¹, which features a large amount of minerals. Aiming to study the capacity of sediment P sorption was conducted adsorption experiments. Data were adjusted by Langmuir and Freundlich equation. For each batch experiment was calculated rate constant (k), the linear coefficient of determination (R²) and the maximum amount of P adsorbed (Qmax). The Langmuir model was suitable to describe the adsorption of P in sediments, because this model showed better linear coefficient of determination (R²). The sediments have yet expressive capacity of phosphate adsorption within the parameters of adsorption isotherms, which can act as a mitigating factor against the significant contribution of phosphorus via raw sewage.